2020
DOI: 10.1016/j.cbpb.2019.110376
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-O acyltransferase 1 is inhibited by gga-miR-181a-5p and gga-miR-429-3p through the TGFβ pathway in endodermal epithelial cells of Japanese quail

Abstract: Sterol-O acyltransferase 1 is inhibited by gga-miR-181a-5p and gga-miR-429-3p through the TGFβ pathway in endodermal epithelial cells of Japanese quail

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In this study, the examination of gene expression in exosomes extracted from 3rd-passage stem cells revealed an upregulation in the expression of these miRNAs, which could reinforce this phenomenon. Furthermore, there are many reports concerning miR141-3p, miR676-3p, miR429-3p, miR379-5p, and miR154-5p, which have been associated with the pathogenesis of various cancers and other disorders [ 77 , 78 , 79 , 80 , 81 ]. Therefore, these miRNAs may play promising roles in reproduction and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the examination of gene expression in exosomes extracted from 3rd-passage stem cells revealed an upregulation in the expression of these miRNAs, which could reinforce this phenomenon. Furthermore, there are many reports concerning miR141-3p, miR676-3p, miR429-3p, miR379-5p, and miR154-5p, which have been associated with the pathogenesis of various cancers and other disorders [ 77 , 78 , 79 , 80 , 81 ]. Therefore, these miRNAs may play promising roles in reproduction and embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…gga-miR-429-3p exhibited the highest number of interactions with target genes involved in influenza A virus-related pathways. gga-miR-429-3p can affect the TGF-beta pathway by regulating the expression level of TGFβ1 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that TGFβ1 upregulates SOAT1 expression during differentiation of monocytes into macrophages [ 27 ]. SMAD3, downstream of TGFβ1, is predicted to bind to the SOAT1 promoter to upregulate SOAT1 expression [ 28 ]. As the TGFβ/SMAD pathway is a major pathway in renal fibrosis in aging, diabetic, and ischemic kidneys [ 29 ], this pathway might also be involved in the upregulation of SOAT1 expression in our model.…”
Section: Discussionmentioning
confidence: 99%